"Kaj z razredom?" - Vezovnik, Andreja (Teorija in praksa, 2011)
This contribution attempts to elaborate on the notion of class. It focuses primarily on the theoretical tradition that runs from Marx via Gramsci and Althusser to the Post-Marxist notion of class as understood in LaclauŽs discourse theory. It concentrates on some key highlights and reflections on the concept of class, leading from an essentialist to a non-essentialist conception of class. It presents their understanding of the notions class, class identity/ subjectivity, hegemony, antagonism, discourse, ideology etc. through the authors mentioned above and seeks to highlight the impact of Marxist theoretical thought on understanding the notion of class in Post-Marxism and cultural studies more broadly.
Keywords: Cultural studies; Kulturne študije; Social classes; Družbeni razredi; Postmarksizem; Postmarxism; Hegemonija; Hegemony